Preparation and Characterization of PSi/Si Electrochemically Formed as Photodetectors - Jbaier, Doaa S (Al-Nahrain Journal of Science, 2018)
Porous silicon were constructed electrochemically with various form ationtimes (5, 10, 15 and 20) min with current density 20mA/cm2 on p-type silicon. The influence of formation time on the structural and morphological properties have been presented by using SEM and optical microscopy. The SEM analysis was showed that the porous silicon layer has a uniform structure and this structure varied with increasing the etching time. The optical microscope was carried out to study the thickness, the pore diameter and etching rate of porous silicon layer, we have found the porous silicon thicknessis accretion with excess the formation time and pores diameter increased also. The etching rate was found to increase from 1.25 to 1.53 μm/min. The electrical properties of PSi samples which represented by I-V characterization under dark show that when the etching time increased the current which pass through the layer of porous silicon decreased because of increasing the resistivity of PSi surface. From I-V charecteristics PSi layer show a good rectification and high responsivity for visible and near IR region.